Pelatihan dan Pendampingan Pembuatan Laporan Keuangan Sederhana UMKM Menggunakan Ms. Excel di Warung Ikan Bakar Kiraha - Willinjilani Sepdika; Endang Sri Utami (Lembaga Pengembangan Kinerja Dosen, 2023)
Financial reports are important for MSME actors because they allow them to know their business finances and understand whether their business is profitable or losing money. In addition, the problem with the Kiraha’s Grilled Fish Stalls shop is the lack of understanding in compiling financial reports. In this service, the methods are Surveys, Training and Assistance, and Outcomes. As a result of this dedication, the recording of the financial reports of Kiraha’s Grilled Fish Stalls is still manual and does not separate financial reporting between capital, income, expenses and personal interests, so that the financial reports of Kiraha’s Grilled Fish Stalls are still not optimal. every month, unknown profits and even losses obtained. Therefore the servant provides assistance in the form of training or direction on how to record financial reports correctly using Microsoft Excel to facilitate the recording of financial reports and ensure the continuity of the business of MSME actors Kiraha’s Grilled Fish Stalls.